Analysis of the problem of monitoring the concentration of Carbon Dioxide in Smart Home. Methods for measuring Carbon Dioxide (Моделювання, керування та інформаційні технології, 2023)
The demand for efficient environmental monitoring rises as smart houses become increasingly interwoven into our daily lives. The carbon dioxide concentration is one of the most crucial variables for indoor air quality and energy efficiency. This article addresses several ways for measuring carbon dioxide levels, including measurements with chemical, optical, and electrochemical sensors, as well as the difficulties that come with carbon dioxide monitoring in smart homes. Users can choose carbon dioxide monitoring solutions for smart home systems in an informed manner by being aware of the advantages and disadvantages of different techniques.